2019
DOI: 10.5937/fmet1902253r
|View full text |Cite
|
Sign up to set email alerts
|

Design of a board game with augmented reality

Abstract: This paper presents the design process of a board game with augmented reality. The board games have remained attractive in this time of complete digitalization. The experience of hands on play has been the key feature of the board game. By introducing AR in the board games this key feature is kept together with digitalization of some elements of the gameplay. Augmented reality games provide players with a rich and potentially unlimited range of interaction possibilities. Implementation of AR creates added valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 16 publications
0
0
0
Order By: Relevance
“…The results of the validation from experts showed that 92.5 percent was in a very valid category so it was very feasible to try out. The same was conveyed in the study (Rizov et al, 2019;Tsai et al, 2021) noted some disagreement based on utility. (1) Equal distribution of learning content (2) Clearer and more interesting learning process (3) More interactive learning process (4) Efficiency of time and effort (5) Improving the quality of learning outcomes (6) The role of the media in the learning process can be done anytime, anywhere.…”
Section: Discussionmentioning
confidence: 63%
“…The results of the validation from experts showed that 92.5 percent was in a very valid category so it was very feasible to try out. The same was conveyed in the study (Rizov et al, 2019;Tsai et al, 2021) noted some disagreement based on utility. (1) Equal distribution of learning content (2) Clearer and more interesting learning process (3) More interactive learning process (4) Efficiency of time and effort (5) Improving the quality of learning outcomes (6) The role of the media in the learning process can be done anytime, anywhere.…”
Section: Discussionmentioning
confidence: 63%